(untitled) (International Journal of Engineering and Computer Science, 2015)
It is believed that there are currently millions of vehicles on the roads worldwide. The over speed of vehicles ,theft of vehicles, disobeying traffic rules in public, an unauthorized person entering the restricted area are keep on increasing. Edge is a basic feature of image. The image edges include rich information that is very significant for obtaining the number plate detection based on morphological operations by object recognition. This paper reveals about the design and development of automatic number plate recognition. Dynamic image processing techniques are used for recognizing the license plate numbers from an image containing it. Recognition of license plate in a picture which is prone to illumination problems is done using this process. We need an automatic public security system. Each vehicle has their own Vehicle Identification Number („VIN‟) as their primary identifier. The VIN is actually a License Number which states a legal license to participate in the public traffic. The proposed paper is to identify the vehicle with the help of vehicles License Plate (LP).LPRS is one the most important part of the Intelligent Transportation System (ITS) to locate the LP. In this paper certain existing algorithm drawbacks are overcome by the proposed morphological operations for LPRS. Morphological operation is chosen due to its higher efficiency, noise filter capacity, accuracy, exact localization of LP and speed.